Foucault e a crítica genealógica: uma investigação da governamentalidade política - Helrison Silva Costa (2017)
Starting from the micropolitical aspects in the social tangle Foucault attemps his analysis on capillary dimension in wich a multiplicity of power relations and political technologies emerges, whose historical traces can be genealogically pursued. From the course Securité, Territoire, Population gived by Foucault at the Collège de France em 1977-1978 one sees an extension of the objects of study of the philosopher who proceeds to investigate the process of governmentalization of society and the State since the sixteenth century whith the policies of reason of State - anchored in two security technologies: the diplomatic-military device and the police and the liberal governmentality based on a scientific rationality and an economic government that affects the population. These rationalized pratices of government go back to the implementation of the pastoral power developed by the Catholic Church since the third century, responsible for coining the idea of a government over individuals. At the beginnig of modernity, the techniques of government of pastoral power go beyond the religious sphere in wich they were circumscribed by the crisis introduced by the counter-conducts that arise in opposition to the attacks of the pastoal power over the modes of individuals conduct, wich puts in evidence the question about how to govern. Unfold from this, the formulation of the notion of critical atitude understood as the behavior that caracterizes the action of the individuals in front of the investments of power inquiring about the way in wich one is governed and in limiting the avance of the rationalized government practices. From the considerations about the critical attitude Foucault draws the idea of a critical project that claims an affiliation with the Kants thought, but that takes place on the auspices of the genealogical method bequeathed by Nietzsche, wich lends itself to the studies of the pratices of power in its historical dimension. Thus, we shall dwell on the analysis of what Foucault understands by critique in 1978, evidencing the link with genealogy that constitutes genealogical critique, whose the effect is the dismantling of historical ordering schemes that show the conditions of possibility of historical singularities indentified in the arts of government.